PENGARUH HARGA DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SAYURAN HIDROPONIK DI KOTA SORONG : STUDI PASCA PANDEMI COVID 19 - Kasih, Nillam Mutiara; Sofia, Susetyowati; Rokhimah (Yayasan Nuraini Ibrahim Mandiri, 2024)
The purpose of this study was to determine the effect of price and lifestyle on purchasing decisions for hydroponic vegetables in the city of Sorong. The number of samples in this study were 92 respondents and used the saturated sample method. This study uses the method of analysis of multiple linear regression tests. The method of collecting data in this research uses questionnaires and field observations. The findings of this study indicate that the price and lifestyle variables partially or simultaneously have a significant positive influence on the purchasing decision of hydroponic vegetables in the city of Sorong.